ANALISIS KELELAHAN (FATIGUE) PADA HOTMIX RECYCLED ASPHALT (HMRA) - Pradani, Novita (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2012)
Pavement Recycling as alternative technology in pavement construction and maintenance iscontinuously developed due to scarcity and highly cost of materials. The aim of this research is to modifyrecycled material by adding a polymer that is capable to improve the physical properties of bitumen andthe performance of recyled mixture. The asphalt mixture in this research is AC-Wearing Course (AC-WC)which contain Reclaimed Asphalt Pavement (RAP), fresh material and asphalt Pen 60/70. Percentage RAPused is 20% and 30% to the total weight of mixture. Fatigue Performance of mixture was measured using 4-Point Bending Test Apparatus with strain control. The result from bitumen characteristic tests shown that RAPbitumen has lower penetration grade and higher viscosity value. Fatigue test shown that, rising thepercentation of RAP will increase the fatigue resistance of mixture by higher average number of cycles at30% RAP mixture (19307 cycles). Generally, the research shown that RAP can be used as alternativematerial to the pavement rehabilitation. In spite of that attention of maximum RAP percentation in mixtureand construction quality control should be taken into account.